Concentration-effect relationships with carbamazepine and its epoxide on psychomotor and cognitive function in epileptic patients. Issue 7 (July 1988) - Gillham, R A; Williams, N; Wiedmann, K; Butler, E; Larkin, J G; Brodie, M J
Abstract : A battery of psychometric tests was administered to 85 patients with epilepsy, of whom 26 were untreated, 40 received carbamazepine monotherapy and 19 took carbamazepine with another anticonvulsant. Carbamazepine alone had little effect on performance, but carbamazepine polypharmacy produced significant impairment. Increasing concentrations of carbamazepine (four tests) and its active metabolite, carbamazepine 10, 11 epoxide (seven tests), correlated with decreasing performance in the monotherapy patients.